Distribution of Acetogenic Naphthoquinones in Droseraceae and Their Chemotaxonomic Utility - Jan Schlauer; Andreas Fleischmann; Siegfried R. H. Hartmeyer; Irmgard Hartmeyer; Heiko Rischer (Biology, 2024)
Chemotaxonomy is the link between the state of the art in analytical chemistry and the systematic classification and phylogenetic analysis of biota. Although the characteristic secondary metabolites from diverse biotic sources have been used in pharmacology and biological systematics since the dawn of mankind, only comparatively recently established reproducible methods have allowed the precise identification and distinction of structurally similar compounds. Reliable, rapid screening methods like TLC (Thin Layer Chromatography) can be used to investigate sufficiently large numbers of samples for chemotaxonomic purposes. Using distribution patterns of mutually exclusive naphthoquinones, it is demonstrated in this review how a simple set of chemical data from a representative sample of closely related species in the sundew family (Droseraceae, Nepenthales) provides taxonomically and phylogenetically informative signal within the investigated group and beyond.